Changes of Amide Proton Transfer Imaging in Multiple System Atrophy Parkinsonism Type - Li, Shuhua; Chan, Piu; Li, Chunmei; Chen, Haibo; Chen, Min; Su, Wen; Li, Kai; Lu, Na; Yu, Lu; Chu, Defa; Wu, Pu-Yeh (Frontiers in Aging Neuroscience, 2020)
Multiple system atrophy (MSA), an atypical parkinsonism of alpha-synucleinopathies, has no specific biomarker of diagnosis. According to different combinations of symptoms, MSA can be classified as parkinsonism-type MSA (MSA-P) and cerebellar-type MSA (MSA-C; Watanabe et al., 2018). Amide proton transfer (APT) imaging is by far the most studied chemical exchange saturation transfer imaging for its sensitivity to mobile protons and peptides in tissues. We hypothesize that APT imaging may be a feasible biomarker of MSA-P. Twenty MSA-P patients and 20 age-matched normal controls were enrolled in this study and underwent MR exams on a 3.0-T MR scanner. Magnetization transfer spectra at 3.5 ppm were acquired at two transverse slices of the head, including the midbrain and the basal ganglia. Mann–Whitney U test was used to compare the asymmetrical magnetization transfer ratio (MTRasym) difference between MSA-P patients and normal controls. The APT MTRasym values of MSA patients in the red nucleus (RN) (SN; P = 0.000), substantia nigra (P = 0.000), thalamus (P = 0.000), and putamen (P = 0.013) were significantly higher than those in normal controls. There was a negative correlation between APT MTRasym and the score of part III of the Unified Parkinson Disease Rating Scale (R = −0.338, P = 0.044) in the putamen, while there was a positive correlation between the APT MTRasym and the rate of motor symptom progression (R = 0.406, P = 0.017) in the RN. These findings suggest that APT MTRasym changes are found and may be of value in the diagnosis of MSA-P.